Menakar Kembali Kesenian Islam di Indonesia Melalui Seni Komedi dalam Dakwah Islam - Rosanita, Devi (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
Indonesian arts and have diverse characteristics of each. Arts Indonesia has its own appeal for art lovers. However, art that developed in Indonesia has experienced a shift of meaning chiefly Islamic Art. Human resources, which in essence becomes the perpetrator of art, acting far from Islamic values . Thus, the art of comedy is one art that berfunsi to entertain and help merefresing brain in order to relax. Indonesia, the art of comedy is growing and moving rapidly in the entertainment. The art of comedy can be internalized and coupled with the message of Islam, because it seems that preaching in using this approach can capture and invites people especially Muslims in the Islamic religious teachings. Internalization of these two areas were able to move and become Islamic mover. Kesenian Indonesia beragam dan mempunyai ciri khas masing-masing. Kesenian Indonesia mempunyai daya tarik sendiri bagi penikmat seni. Namun, kesenian yang berkembang di Indonesia sudah mengalami pergeseran makna terutamanya kesenian Islam. Sumber daya manusia yang sejatinya menjadi pelaku kesenian, bertindak jauh dari nilai Islam. Maka seni komedi adalah salah satu seni yang berfungsi untuk menghibur dan membantu me-refresh otak agar bisa relax. Indonesia, seni komedi berkembang dan bergerak pesat di dunia hiburan. Seni komedi dapat diinternalisasikan dan digabungkan dengan dakwah Islam, karena tampaknya dakwah dalam menggunakan pendekatan ini bisa menjaring dan mengajak manusia terlebih umat Islam dalam ajaran agama Islam. Internalisasi dua bidang ini mampu menggerakkan dan menjadi Islamic mover.